Adaptive Economy Model: Causes of Origin and Key Features (Journal of Economic Research & Business Administration, 2020)
The modern world is developing dynamically, which is facilitated by changes in technology, preferencesand tastes of consumers, in business models, etc. Companies and even entire sectors of theeconomy have to quickly adapt to various changes in market conditions in order not only to be competitive,but also to survive in the face of uncertainty. The aim of this work is to analyze publications on theexperience of adapting companies to determine the key factors of this dynamic process, as well as justifythe need to develop the theoretical foundations of an adaptive economy model. It is the adaptability ofeconomies that becomes a key condition for the well-being of society. Thus, the main areas of researchare the identification of key factors in the adaptation of companies, industries and the economy as awhole to changes in economic conditions. The research methodology is the analysis and synthesis of scientificpublications. Particular attention is paid to such factors as corporate culture, business model andeconomic institutions. The scientific and practical significance of the work is to identify the dependenceof the adaptability of the economy on the adaptability of entrepreneurship (companies, organizations).The main results of the work can be used to create the theoretical base of the adaptive economy model.It is this model that meets the characteristics of dynamically changing external and internal economicconditions of entrepreneurship.